AUTONOMIC CONTROL OF HEART RATE AFTER EXERCISE IN TRAINED WRESTLERS - Carlos F Henríquez; Eduardo Báez; Astrid Von Oetinger; Rodrigo Cañas; Rodrigo Ramírez (Biology of Sport, 2013)
The objective of this study was to establish differences in vagal reactivation, through heart rate recovery and heart rate variability post exercise, in Brazilian jiu-jitsu wrestlers (BJJW). A total of 18 male athletes were evaluated, ten highly trained (HT) and eight moderately trained (MT), who performed a maximum incremental test. At the end of the exercise, the R-R intervals were recorded during the first minute of recovery. We calculated heart rate recovery (HRR60s), and performed linear and non-linear (standard deviation of instantaneous beat-to-beat R-R interval variability – SD1) analysis of heart rate variability (HRV), using the tachogram of the first minute of recovery divided into four segments of 15 s each (0-15 s, 15-30 s, 30-45 s, 45-60 s). Between HT and MT individuals, there were statistically significant differences in HRR60s (p <0.05) and in the non linear analysis of HRV from SD130-45s (p <0.05) and SD145-60s (p <0.05). The results of this research suggest that heart rate kinetics during the first minute after exercise are related to training level and can be used as an index for autonomic cardiovascular control in BJJW.